Hacia un nuevo modelo de docencia en otorrinolaringologia: propuesta para renovar la metodología de la enseñanza (2013)
The process of updating the medical programs in graduate studies in order to renovate and improve the teaching and learning methods are of great importance in college. This updating activity would give Otolaryngologists teachers helpful tools and facilitate learning to the graduate students (Resident Doctors), both in basic and advanced theoretical areas, and in specific surgical practices that such specialties require in depth because it demands a highly specialized surgical skills needed for the appropriate training of the surgeons who will work in different areas of otolaryngology.